2020
DOI: 10.9739/tjvs.2020.662
|View full text |Cite
|
Sign up to set email alerts
|

Our experiences with hemodialysis arteriovenous fistula aneurysm

Abstract: Objectives: This study presents the short-term clinical data of surgical treatment strategies of patients with hemodialysis arteriovenous fistula (AVF) aneurysms. Patients and methods: Between January 2010 and July 2019, a total of 103 patients (69 males, 34 females; mean age 52.3±20.6 years; range, 18 to 87 years) who underwent elective AVF surgery due to AVF aneurysms (≥4 cm) were included in this retrospective study. Operative techniques and patients' outcomes were reviewed and analyzed. Results: Aneurysm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that the commonly observed complications of AVF are related to an inadequate maturation of AVF, stenosis, aneurysms, infections, thrombosis, high flow rate AVF and steal syndrome resulting from ischaemia. 6 , 25 , 26 Failure of the AVF is mostly associated with stenosis of the artery of the vein. However, these complications can be corrected through endovascular or surgical techniques; thus, shorter segments resulting from stenosis can be treated using percutaneous transluminal angioplasty while surgical replacements are the recommended standards in extensive stenotic segments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the commonly observed complications of AVF are related to an inadequate maturation of AVF, stenosis, aneurysms, infections, thrombosis, high flow rate AVF and steal syndrome resulting from ischaemia. 6 , 25 , 26 Failure of the AVF is mostly associated with stenosis of the artery of the vein. However, these complications can be corrected through endovascular or surgical techniques; thus, shorter segments resulting from stenosis can be treated using percutaneous transluminal angioplasty while surgical replacements are the recommended standards in extensive stenotic segments.…”
Section: Discussionmentioning
confidence: 99%